SC Nixes De Lima bid to quash drug raps - Ramos, Marlon (Philippine Daily Inquirer, 2017)
Voting 9-6, the high tribunal rules that the Muntinlupa Regional Trial Court has jurisdiction over the case. But senators belonging to the minority bloc vow to support an appeal by their colleague.